Kinetic and Structural Characterization of a Heterohexamer 4-Oxalocrotonate Tautomerase from Chloroflexus aurantiacus J-10-fl: Implications for Functional and Structural Diversity in the Tautomerase Superfamily - Burks, Elizabeth A. (2010)
4-Oxalocrotonate tautomerase (4-OT) isozymes play prominent roles in the bacterial utilization of aromatic hydrocarbons as sole carbon sources. These enzymes catalyze the conversion of 2-hydroxy-2,4-hexadienedioate (or 2-hydroxymuconate) to 2-oxo-3-hexenedioate, where Pro-1 functions as a general base and shuttles a proton from the 2-hydroxyl group of substrate to the C-5 position of product. 4-OT, a homohexamer from Pseudomonas putida mt-2, is the most extensively studied 4-OT isozyme and the founding member of the tautomerase superfamily. A search of five thermophilic bacterial genomes identified a coded amino acid sequence in each that had been annotated as a tautomerase-like protein but lacked Pro-1. However, a nearby sequence has Pro-1, but the sequence is not annotated as a tautomerase-like protein. In order to characterize this group of proteins, two genes from Chloroflexus aurantiacus J-10-fl were cloned, and the corresponding proteins expressed. Kinetic, biochemical, and X-ray structural analysis show that the two expressed proteins form a functional heterohexamer 4-OT (hh4-OT), composed of three αβ dimers. Like the P. putida enzyme, the hh4-OT requires the amino-terminal proline and two arginines for the conversion of 2-hydroxymuconate to product, implicating an analogous mechanism. In contrast to 4-OT, the hh4-OT does not exhibit the low-level activity of another tautomerase superfamily member, the heterohexamer trans-3-chloroacrylic acid dehalogenase (CaaD). Characterization of the hh4-OT enables functional assignment of the related enzymes, highlights the diverse ways the β–α–β building block can be assembled into an active enzyme, and provides further insight into the molecular basis of the low level CaaD activity in 4-OT.